The relationship between family environments growing up and behavioral health among LGBTQ+ adults: The mediating role of internalized homonegativity - Pin-Chen Chiang; Yinuo Xu; Denise Yookong Williams; Ankur Srivastava; Jake A. Leite; Adam R. Englert; William J. Hall (PLoS ONE, 2025)
Purpose Disparities in the behavioral health outcomes for lesbian, gay, bisexual, transgender, and queer+ (LGBTQ+) adults—such as depression, anxiety, and alcohol use—are often attributed to experiences of discrimination, victimization, and lack of supportive environments, including hetero- and cis-normative family settings. Yet, how family environments in childhood influence LGBTQ+ adults’ behavioral health and internalized homonegativity has not been extensively examined. Methods This study utilized a U.S. national dataset of LGBTQ+ adults (N = 499). Data were collected in November 2020 using an online survey. A series of multivariate ordinary least squares regression models and Sobel tests were performed. Results Results showed that as homophobic messages from family increased, levels of depression (β = .19, p < .001), anxiety (β = .17, p < .001), and internalized homonegativity (β = .13, p < .01) increased. As the conservatism level in families increased, levels of alcohol use (β = .11, p < .05), and internalized homonegativity (β = .15, p < .01) increased. In the mediation analysis, internalized homonegativity was found to partially mediate the relationship between homophobic messages from family and depression (z = 3.35, p < .001), homophobic messages and anxiety (z = 3.09, p < .01), and conservatism in family and alcohol use (z = 2.80, p < 0.01). Internalized homonegativity also fully mediated the relationship between homophobic messages and alcohol use (z = 2.66, p < 0.01), conservatism in family and depression (z = 3.76, p < 0.001), and conservatism in family and anxiety (z = 3.45, p < 0.001). Conclusion Study findings underscore the importance of inclusive climates within a family and internalized homonegativity as a mediator for LGBTQ+ individuals’ behavioral health. Implications for intervention and future research are discussed.